Net Social Expenditure - Adema, Willem (OECD Labour Market and Social Policy Occasional Papers, 1999)
This paper contains an overview of net total (public and private) social expenditure indicators. These indicators have been developed to supplement available historical information on gross social expenditure trends by accounting for the varying impact of the tax system across countries. Tax systems can affect social spending in three ways: Governments levy direct taxes and social security contributions on cash transfers. Governments levy indirect taxes on goods and services bought by benefit recipients. And, Governments may award tax advantages similar to cash benefits and/or grant tax concessions aiming to stimulate purchase of insurance coverage by private agents. The paper summarises the methodological framework as previously developed, but extends coverage to thirteen countries for which information for 1993 and/or 1995 is now available: Australia, Belgium, Canada, Denmark, Finland, Germany, Ireland, Italy, the Netherlands, Norway, Sweden, the United Kingdom ...